Impact of Elevated Progesterone in Late Follicular Phase on Early Pregnancy Outcomes and Live Birth Rate After Fresh Embryo Transfers - Xu, Yueming; Zhang, Jie; Li, Aimin; Yang, Ni; Cui, Na; Hao, Guimin; Gao, Bu-Lang (Frontiers in Cell and Developmental Biology, 2022)
Objective: To investigate the effect of progesterone elevation during late follicular phase on early pregnancy outcomes and live births after fresh embryo transfers. Methods: Patients who underwent IVF/ICSI treatment cycles were retrospectively enrolled. The effect of progesterone elevation was analyzed on early pregnancy outcome and live births after fresh embryo transfers. Results: A total of 2,404 patients were enrolled on the day of HCG triggering (HCG0), 1,584 patients on the day before HCG triggering (HCG-1), and 800 patients 2 days before HCG triggering (HCG-2). With a 1 ng/ml increase in the progesterone level on HCG0 day when the progesterone level was ≥1.5 ng/ml, the clinical pregnancy rate decreased by 60% (95% CI: 0.2–0.7, p = 0.004), the intrauterine pregnancy rate decreased by 70% (95% CI: 0.2–0.7, p = 0.003), and the live birth rate decreased by 70% (95% CI: 0.1–0.7, p = 0.004). With a 1 ng/ml increase in the progesterone level on HCG-1 day, the clinical pregnancy rate decreased by 90% (95% CI: 0.0–0.5, p = 0.003) when the progesterone level was ≥1.6 ng/ml, the intrauterine pregnancy rate decreased by 90% (95% CI: 0.0–0.5, p = 0.001) when the progesterone was ≥1.5 ng/ml, and the live birth rate decreased by 90% (95% CI: 0.0–0.6, p = 0.015) when the progesterone was ≥1.7 ng/ml. On HCG-2 day when the progesterone was ≥1.2 ng/ml, the clinical pregnancy rate decreased by 80% (95% CI: 0.1–0.6, p = 0.003), and the intrauterine pregnancy rate decreased by 70% (95% CI: 0.1–0.7, p = 0.007) with a 1 ng/ml increase in the progesterone level. Conclusion: Elevated progesterone level during the late follicular phase is an independent risk factor affecting the clinical pregnancy rate, intrauterine pregnancy rate, and live birth rate among infertile patients undergoing IVF/ICSI after fresh embryo transfers. When the progesterone level exceeds a certain level, the early pregnancy and live birth rates after fresh embryo transfers show a rapid downward trend.